Inulin-type fructans change the gut microbiota and prevent the development of diabetic nephropathy - Liman Luo; Jinlan Luo; Yueting Cai; Menglu Fu; Wenhua Li; Lili Shi; Jingrui Liu; Ruolan Dong; Xizhen Xu; Ling Tu; Yan Yang (Elsevier, 2022)
Diabetic nephropathy (DN) is the most common cause of end-stage renal disease, and few treatment options that prevent the progressive loss of renal function are available. Studies have shown that dietary fiber intake improves kidney diseases and metabolism-related diseases, most likely through short-chain fatty acids (SCFAs). The present study aimed to examine the protective effects of inulin-type fructans (ITFs) on DN through 16 S rRNA gene sequencing, gas chromatographymass spectrometry (GCMS) analysis and fecal microbiota transplantation (FMT). The results showed that ITFs supplementation protected against kidney damage in db/db mice and regulated the composition of the gut microbiota. Antibiotic treatment and FMT experiments further demonstrated a key role of the gut microbiota in mediating the beneficial effects of ITFs. The ITFs treatment-induced changes in the gut microbiota led to an enrichment of SCFA-producing bacteria, especially the genera Akkermansia and Candidatus Saccharimonas, which increased the fecal and serum acetate concentrations. Subsequently, acetate supplementation improved glomerular damage and renal fibrosis by attenuating mitochondrial dysfunction and reducing toxic glucose metabolite levels. In conclusion, ITFs play a renoprotective role by modulating the gut microbiota and increasing acetate production. Furthermore, acetate mediates renal protection by regulating glucose metabolism, decreasing glycotoxic product levels and improving mitochondrial function.